Peran Ranting Muhammadiyah dalam Menyelenggarakan Pendidikan untuk Masyarakat di Desa Kacangan Kecamatan Andong Tahun 2015 - Fitriyana, Leny; Drs. Arif Wibowo, M.Ag., Drs. Arif Wibowo, M.Ag (2016)
Muhammadiyah branch of Kacangan village is one of most active Muhammadiyah branches under Muhammadiyah Unit of Kecamatan Andong. The Muhammadiyah branch of Kacangan village has been showing efforts in community education sector, although only minor local people of the village were members of Muhammadiyah organization. Muhammadiyah is an Islamic organization with principle of amar ma'ruf nahi munkar and tadjid. The Islamic organization had been founded with goal of enforcing and upholding Islam religion in order to realize the true Islamic society. Efforts of achieving the goals performed in Muhammadiyah of Kacangan village involved: 1) establishment of Islamic environment, 2) finding cadres from local inhabitants, and 3) embedding Islam religion in local people early. The efforts have been performed by establishing education institutions, both formally and informally, aimed at people of all ages. Based on the background, so purpose of the research is to describe roles of Muhammadiyah branch of Kacangan village in performing education for local community of Kacangan village, Kecamatan Andong of 2015 and also, obstacles facing the efforts. The research is a field research with descriptive-qualitative approach. Data of the research was obtained by using interview, documentation and observation methods. Then, the data was analyzed by using deductive-inductive method. Based on results of the research, it can be concluded that Muhammadiyah branch of Kacangan village had important role in performing education for local people. Forms of the education performance consisted of formal and informal educations such as Play Group Aisyiyah (KB Aisyiyah), Aisyiyah Kindergarten, MI Muhammadiyah, Diniyah Muhammadiyah, daily Qur'an recitation and monthly Qur'an recitation for people of all ages. Obstacles facing the efforts were: a) majority of villagers were members of nahdiyin, thus automatically most students of Muhammadiyah education institution were member of Nahdlatul Ulama (NU) organization, b) local people had less attention to education, it can be seen from many school aged children had terminated their educations and, c) average villagers were low to moderate classes of socioeconomic .